High-performance all-solid-state Li2S batteries using an interfacial redox mediator. Issue 2 (20th January 2023) - Kwok, Chun Yuen; Xu, Shiqi; Kochetkov, Ivan; Zhou, Laidong; Nazar, Linda F.
Abstract : We report a Li2 S/LiVS2 core–shell nano-architecture design for all-solid-state Li2 S batteries where the LiVS2 shell serves as both a Li + /e − transport vehicle and redox mediator for Li2 S on charge to help overcome sluggish cathode kinetics. Abstract : All-solid-state Li–S batteries based on lithium sulfide cathodes have generated much excitement as possible next-generation energy storage candidates because they can offer a high theoretical energy density exceeding that of lithium-ion batteries, and the possibility of "anode-less" cell designs. However, solid-state Li2 S cathode kinetics are hindered by both limited ionic and electronic transport and a high activation barrier on charge. Here we report a Li2 S/LiVS2 core–shell cathode architecture design, whereby the shell serves as both a charge-carrier transport vehicle and electron transfer mediator for Li2 S during oxidation. With an argyrodite-type solid electrolyte, the solid-state Li2 S cell exhibits very good rate capability up to 3 mA cm −2 at room temperature, and nearly 80% capacity retention up to 1000 cycles at a moderate current density of 1 mA cm −2 . High active material loading (4 and 6 mg cm −2 ) is demonstrated in this configuration with stable capacity retention. High areal capacity up to 5.3 mA h cm −2 with a very high active material loading of 10 mg cm −2 is also reported, albeit with limited cycle life.